The effect of some types of cooperative learning strategies on learning the skill of scoring in football for second-year intermediate students. (Journal of the College of Basic Education, 2023)
The impact of educational units according to the patterns of the cooperative learning strategy in learning football scoring for second-year middle school students. The study aimed to design and apply educational units according to the three cooperative learning strategy patterns (nested groups, network learning, and research group) in learning football scoring. Identifying the effect of the three cooperative learning strategy types (interactive groups, network learning, and learning together) in learning football scoring for the three experimental research groups. Identifying which of the three styles is best in learning football scoring. The second chapter included many theoretical and interrelated studies. The researcher used experimental research to suit the objectives, hypotheses, and procedures of the research. The researcher identified the research population in an intentional manner of students from Al-Naimiya Middle School for Boys in the Fallujah Department in the Anbar Education Directorate for the academic year 2022 - a total number of 92 students from three. Section (A) has 30 students, Section (B) has 32 students, and Section (C) has 30 students. As for the research sample, the researcher divided the sample into three research groups, with 10 students for each group. The first group taught in the nested group style, the second group in the network learning style, and the third group in the network learning style. Learning together. The researcher extracted procedures for homogeneity and equivalence. One of the most important research procedures was to design three educational units according to the three styles, two units per week with a duration of 45 minutes. The post-test was conducted and the researcher used the statistical bag. The most important conclusions of the research were that using the cooperative learning strategy had a significant impact on teaching football scoring. The cooperative learning strategy generates opportunities for students to practice leadership, and one of the most important recommendations is to emphasize the use of cooperative learning strategies in its multiple styles in teaching football scoring. The use of a cooperative learning strategy in the style of overlapping groups in scoring and handling, and the use of the network learning style and learning together in dribbling and putting down. Emphasis on the use The strategy of cooperative education when teaching middle school students in particular, because it enhances the spirit of communication and teamwork among team members.